Depletion of Ly6G-expressing neutrophilic cells leads to altered peripheral T-cell homeostasis and thymic development in neonatal mice - Rühle, Jessica; Ginzel, Marco; Dietz-Ziegler, Stefanie; Schwarz, Julian; Lajqi, Trim; Beer-Hammer, Sandra; Poets, Christian F.; Gille, Christian; Köstlin-Gille, Natascha (International journal of molecular sciences, 2023)
Newborns and especially preterm infants are much more susceptible to infections than adults. Due to immature adaptive immunity, especially innate immune cells play an important role in a newborn’s infection defense. Neonatal neutrophils exhibit profound differences in their functionality compared to neutrophils of adults. In particular, neonates possess a relevant population of suppressive neutrophils, which not only inhibit but also specifically modulate the function of T-cells. In this study, we investigated whether neonatal neutrophils are already involved in T-cell development in the thymus. For this purpose, we used a newly developed model of antibody-mediated immune cell depletion in which we administered a depleting antibody to pregnant and then lactating dams. Using this method, we were able to sufficiently deplete Ly6G-positive neutrophils in offspring. We demonstrated that the depletion of neutrophils in newborn mice resulted in altered peripheral T-cell homeostasis with a decreased CD4+/CD8+ T-cell ratio and decreased expression of CD62L. Neutrophil depletion even affected T-cell development in the thymus, with increased double positive thymocytes and a decreased CD4+/CD8+ single positive thymocyte ratio. Altogether, we demonstrated a previously unknown mechanism mediating neutrophils’ immunomodulatory effects in newborns.